Predictors of purchase intention among Georgian millennials - Khaburdzaniya, Luara (2021)
Given Master’s thesis evaluates the predictors of purchase intention among Georgian millennials. The main goals of the thesis are to identify key influencing factors of intention to purchase online in Georgian millennials and assess which factors influence the leading ecommerce industries available on the Georgian market. To reach the primary goal of the given thesis, quantitative methods were conducted. The theoretical part of the thesis evaluates literature studies about consumer behaviour as a general approach, online shopping, main trends millennials follow while shopping online, and a general overview of the Georgian economy and Georgian e-commerce market. From evaluated studies, several hypotheses are stated about influencing factors of online purchase intention for Georgian millennials. To test the hypotheses, survey and SPSS regression analysis methods were used. Results from the given methods suggest that Georgia’s primary leading industry that is already well developed in Georgia is the market of electronics. As for a new emerging industry, the online rental marketplace has the most considerable potential. Regression analysis also stated a detailed relationship between dependent and independent variables. It was concluded that the most influential variables for purchasing intentions online among Georgian millennials were gender and major occupation/employment status. The findings of the given Master’s thesis can be used to improve the online marketplace in Georgia, develop a better customer experience on ecommerce, and be part of recommendations for emerging marketers.